Combined ergonomic exposures and development of musculoskeletal pain in the general working population: A prospective cohort study - Lars L Andersen; Jonas Vinstrup; Emil Sundstrup; Sebastian V Skovlund; Ebbe Villadsen; Sannie V Thorsen (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVE: This study aimed to investigate the importance of combined ergonomic exposures at work for the development of musculoskeletal pain. METHODS: Through four rounds (2012-2018) of the Work Environment and Health in Denmark Study, 18 905 employees of the general working population replied to a baseline and 2-year follow-up questionnaire. First, a k-means cluster analysis of seven ergonomic factors (back bending, arm above shoulders, lifting etc., from 'never' to 'almost all the time') identified nine naturally occurring clusters. Second, using a weighted survey regression model controlling for age, gender, survey year, education, lifestyle, influence at work, and pain intensity at baseline, we estimated development of pain intensity (0-10) in the neck-shoulder and low-back in these clusters. The largest cluster served as reference to the other clusters and was characterized by low ergonomic exposures. RESULTS: Clusters characterized by multiple combined ergonomic exposures for a relatively high percentage of the working time showed the largest increase in neck-shoulder as well as low-back pain intensity from baseline to follow-up. However, clusters characterized by high exposure to a few specific ergonomic factors also increased pain significantly, eg, standing/walking combined with lifting/carrying or twisted/bent back for the majority of the working time increased low-back pain, whereas repetitive arm movements for the majority of the working time with or without standing/walking increased neck-shoulder pain. CONCLUSION: Combined occupational ergonomic exposures play an important role in the development of musculoskeletal pain. Workplace preventive approaches should consider this in risk assessments and organization of the work.